Pengaruh Pengetahuan Awal, Kecerdasan Emosional, Dan Motivasi Belajar Terhadap Hasil Belajar IPA Siswa Kelas VIII SMP Negeri 3 Parigi - Lilyanti M. Payung; Achmad Ramadhan; I Made Budiarsa (Universitas Tadulako, 2016)
The aimed of this Research to describe the effect of: (1) Students’s prior knowledge toward the science achievement; (2) emotional quotient toward the science achievement; (3) learning motivation toward the science achievement; and (4) prior knowledge, emotional quotient, and learning motivation toward the science achivement at class VIII of SMPN 3 Parigi. The population of the research was the students at class VIII of SMPN 3 Parigi registered in 2014/2015, consisted of 50 students. The sample of the the research was overall of the population member (saturated sample). The collecting data used multiple choice test to measure the student’s prior knowledge and questionnaire to measure emotional quetiont and student’s learning motivation. The data were analyzed by using double linear regression analyses with SPSS-17. The research findings indicated that there were significant effect between (1) prior knowledge toward the science achievement, (2) emotional quotient toward the science achievement, (3) learning motivation toward science achievement, (4) prior knowledge, emotional quotient, and learning motivation toward the science achivement at class VIII of SMPN 3 Parigi.